Roll of thunder, hear my cry - Taylor, Mildred D; Nelson, Kadir; Woodson, Jacqueline (New York, NY Dial Books for Young Readers, 2016)
A black family living in Mississippi during the Depression of the 1930s is faced with prejudice and discrimination which its children do not understand
Photographs on endpapers
Newbery Medal, 1977
1
Keywords: African Americans -- Juvenile fiction; JUVENILE FICTION / Historical / United States / General; JUVENILE FICTION / People & Places / United States / African American; African Americans -- Fiction; Depressions -- 1929 -- Fiction; Prejudices -- Fiction; Race relations -- Fiction; Mississippi -- History -- 20th century -- Fiction